Theory of Mind and the Action Observation Network : Exploring the roles of beta, alpha, and mu suppression in perspective-shifting, mental state representation, and motor prediction - Kline, Sarah (My University, 2024)
Theory of Mind, the ability to make judgments about another’s mental state, plays a crucial role in social communication and has been linked to various brain processes, including mindreading, mental state ascription, cognitive empathy, and perspective-taking. The Action Observation Network refers to a collection of brain regions that interpret the meaning underlying observed actions by matching them to our own- these sensorimotor regions are engaged during both the observation and execution of a motor action. Mu and beta desynchronization in the Action Observation Network, as measured through non-invasive EEG imaging, have been theorized to play a role in the process of interpreting socially relevant stimuli – specifically concerning processes like emotional empathy, social cognition, and social perception – but many researchers are divided as to what these signals can tell us about social behavior. Additionally, research linking these signals from the Action Observation Network to the Theory of Mind and perspective-switching processes is limited; there are few studies to directly study this phenomenon through the use of mu/beta suppression and dynamic video stimuli. This study will investigate the relationship between mu and beta suppression in the Action Observation Network and mental state attribution in a series of perspective-switching tasks designed to engage the Theory of Mind faculties. In this experiment, subjects were asked to complete a series of social cognitive tasks with varying demands for action context, perspectives, and expectations. The study was unable to identify consistently significant changes in mu/beta across conditions but found a significant change in occipital alpha depending on the context of interaction, supporting previous findings that researchers should exercise caution and account for the effects of attention when designing social cognition tasks for mu suppression.
Keywords: Theory of Mind, Social Cognition, mu suppression, beta suppression, Action Observation Network, EEG, Perspective-Taking